2020
DOI: 10.1093/sleep/zsaa196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mandibular advancement on tongue dilatory movement during wakefulness and how this is related to oral appliance therapy outcome for obstructive sleep apnea

Abstract: Study Objectives To characterise how mandibular advancement splint (MAS) alters inspiratory tongue movement in people with obstructive sleep apnoea (OSA) during wakefulness and whether this is associated with MAS treatment outcome. Methods 87 untreated OSA participants (20 women, apnoea hypopnoea index (AHI) 7-102events/hr, aged 19-76years) underwent a 3T MRI with a MAS in situ. Mid-sagittal tagged images quantified inspirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…MRI and EMG experiments were performed an average of 2.5 ± 2.5 [0.0-12.1] weeks apart. Inspiratory tongue movement and patterns have been described previously in controls and OSA participants (Juge, Knapman et al, 2020).…”
Section: Regional Inspiratory Tongue Dilatory Movement and Emg Associ...mentioning
confidence: 81%
See 4 more Smart Citations
“…MRI and EMG experiments were performed an average of 2.5 ± 2.5 [0.0-12.1] weeks apart. Inspiratory tongue movement and patterns have been described previously in controls and OSA participants (Juge, Knapman et al, 2020).…”
Section: Regional Inspiratory Tongue Dilatory Movement and Emg Associ...mentioning
confidence: 81%
“…Still, during wakefulness, it has been reported that both phasic inspiratory and tonic components of genioglossus EMG may be higher in people with OSA than in healthy control participants (Fogel et al, 2001), possibly to counteract the increased negative pressure in the upper airway during inspiration in people with OSA. Inspiratory airway dilatation during wakefulness is larger in those with narrower airways (Cheng et al, 2014) and with OSA (Juge, Knapman et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations